2018
DOI: 10.1093/mnras/sty3508
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of theGaiaphase space spirals from bending waves

Abstract: We discuss the physical mechanism by which pure vertical bending waves in a stellar disc evolve to form phase space spirals similar to those discovered by Antoja et al. in Gaia Data Release 2. These spirals are found by projecting Solar Neighbourhood stars onto the z − v z plane. Faint spirals appear in the number density of stars projected onto the z − v z plane, which can be explained by a simple model for phase wrapping. More prominent spirals are seen when bins across the z − v z plane are coloured by medi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 37 publications
(49 reference statements)
7
61
0
Order By: Relevance
“…The phase overlap between the observed density and metallicity asymmetries can satisfactorily be explained by the phase-space wrapping of stars in the Z-V Z plane, which has recently been discovered by Gaia (Antoja et al 2018;Binney & Schönrich 2018;Bland-Hawthorn et al 2019;Darling & Widrow 2019;Laporte et al 2019).…”
Section: Summary and Discussionmentioning
confidence: 66%
“…The phase overlap between the observed density and metallicity asymmetries can satisfactorily be explained by the phase-space wrapping of stars in the Z-V Z plane, which has recently been discovered by Gaia (Antoja et al 2018;Binney & Schönrich 2018;Bland-Hawthorn et al 2019;Darling & Widrow 2019;Laporte et al 2019).…”
Section: Summary and Discussionmentioning
confidence: 66%
“…Therefore, the V R colorcoded phase space shears into a spiral that differs from the V φ color-coded phase space spiral in the tightness of the winding (Binney & Schönrich 2018). Different simulations also indicate that the coupled motions in horizontal and vertical directions lead to clear snail shells in V R and V φ colorcoded phase spaces (Darling & Widrow 2019;Laporte et al 2019). In particular, the bar buckling perturbation scenario predicts the most clear snail shell in V R color-coded phase space (Khoperskov et al 2019).…”
Section: Phase Mixing In Colder and Hotter Orbitsmentioning
confidence: 99%
“…1c in Antoja et al 2018), which was suggested to indicate the tight correlation between the in-plane and vertical motions. The two motions are clearly entangled, but there are still important details to be clarified (Binney & Schönrich 2018;Darling & Widrow 2019). Laporte et al (2019) found snail shell at different stellar age bins, and the shape of the snail changes systematically across the Galactic disk.…”
Section: Introductionmentioning
confidence: 99%
“…Gaia data have already revealed signatures of nonequilibrium and ongoing vertical phase mixing in the Milky Way disc , likely induced by a previous pericentric passage of the Sagittarius dwarf galaxy Bland-Hawthorn et al 2019;Haines et al 2019) or by inter-Here be dragons, a phrase famous in medieval cartography when dragons and sea monsters used to designate uncharted and possibly dangerous regions. nally driven bending waves (Khoperskov et al 2019;Darling & Widrow 2019). A large number of kinematic arches with various morphologies not known prior to Gaia were found (Ramos et al 2018) and large-scale wiggles were discovered in the V φ −R plane Antoja et al 2018).…”
Section: Introductionmentioning
confidence: 96%